Independent Curriculum Reform in High School Historical Thinking Skills - Kuwoto, M. Ari; Isrina Siregar; Refli Surya Barkara; Rizki Ananda Hasibuan; Muhammad Afrillyan Dwi Syahputra; Ria Rafianti; Nadia Ramona (Jurnal Pendidikan Indonesia, 2024)
Many teachers still have difficulty implementing learning strategies that can develop historical thinking skills, such as critical, analytical, and reflective thinking. This study aims to create a curriculum programmed by the Ministry of Education, Culture, Sports, Science and Technology. This study uses qualitative research with a descriptive approach and the naturalistic inquiry research method. The research data were obtained from observation, interviews, and documentation. Data analysis techniques include data collection, reduction, presentation, and concluding. The results of this study show that curricular learning consists of an assessment of history teaching and learning activities integrated into the learning process, and a structured summative assessment schedule is determined according to its evaluation. Implementation barriers and solutions will be seen when the RPP or teaching modules are not applied in classroom learning activities. Therefore, the Merdeka Curriculum must implement ATP, CP, and teaching modules. The Merdeka Curriculum provides more space for a learning approach emphasising critical thinking. This allows students to delve deeper into historical analysis and source evaluation and understand the historical context more deeply. The study concludes that the Independent Curriculum improves the quality of history learning in high schools, focusing more on critical thinking and analysis skills.